2015
DOI: 10.1166/jnn.2015.10022
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of IC<SUB>70</SUB>BA and Their Photovoltaic Performance in Polymer Solar Cells

Abstract: Indene-C70 derivatives were synthesized, including indene-C70 mono-adduct (IC70MA), indene-C70 bis-adduct (IC70BA) and indene-C70 tris-adduct (IC70TA). All as-prepared fullerene adducts are in fact a mixture of isomers. The IC70BA mixture was further separated by high-performance liquid chromatography (HPLC) and two different IC70BA isomers were obtained. With the addition of the increased number of indene, the lowest unoccupied molecular orbital (LUMO) energy level of the C70 derivatives is also increased. IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It is noteworthy that there are a handful of other studies in the literature that reported on chromatographic separation of fullerene bisadduct isomers [ 8 , 12 14 ]. To the best of our knowledge, this is the first comprehensive analysis of IC 70 BA mixture using HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that there are a handful of other studies in the literature that reported on chromatographic separation of fullerene bisadduct isomers [ 8 , 12 14 ]. To the best of our knowledge, this is the first comprehensive analysis of IC 70 BA mixture using HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…The C 70 –indene bisadducts C 70 (C 9 H 8 ) 2 (C 70 ind 2 ; and often-abbreviated IC 70 BA) make up one of the presentable series of the regioisomeric C 70 derivatives. It should be noted that C 70 ind 2 had been used in photovoltaics as a mixture, ,, but their synthesis, separation, and separate testing in OSCs have been performed in a current work . Though this is an undoubted breakthrough in the field, the C 70 ind 2 regioisomers have been isolated as fractions containing one major isomer with admixtures of the minor ones.…”
Section: Resultsmentioning
confidence: 99%
“…Widely studied C 60 and C 70 fullerene derivatives, such as PC 61 BM (Phenyl C 61 butyric acid methyl ester) or PCBM‐like fullerenes,,,,,,, indene modified fullerenes,,,, and (di‐)hydronaphthyl modified fullerenes,,,, have been used in different device architectures. While there are many papers describing the effect of fullerene mono‐ and multi‐adducts on the performance of an organic solar cell (see refs ,.…”
Section: Introductionmentioning
confidence: 99%
“…,,,. Especially for C 70 derivatives only a small number of papers can be found in literature in which the electrochemical behavior of rather few isolated fullerene derivatives are described ,,,…”
Section: Introductionmentioning
confidence: 99%